First Report of Tumor Treating Fields (TTFields) Therapy for Glioblastoma in Comorbidity with Multiple Sclerosis - Rebecca Kassubek; René Mathieu (Brain Sciences, 2022)
Tumor Treating Fields (TTFields) therapy is FDA approved and has the CE mark for treatment of newly diagnosed and recurrent glioblastoma. To our knowledge, to date TTFields therapy remains unstudied in glioblastoma patients with multiple sclerosis (MS) as a comorbidity. Here, we present a patient who was diagnosed with MS at the age of 34. Treatment included several corticoid pulse treatments and therapies with interferon beta-1a and sphingosine-1-phosphate receptor modulator fingolimod. At the age of 52 the patient was diagnosed with glioblastoma, after experiencing worsening headaches which could not be attributed to the MS condition. After subtotal resection and concomitant radiochemotherapy, the patient received temozolomide in combination with TTFields therapy. For two years, the tumor condition remained stable while the patient showed high adherence to TTFields therapy with low-grade skin reactions being the only therapy-related adverse events. After two years, the tumor recurred. The patient underwent re-resection and radiotherapy and restarted TTFields therapy together with chemotherapy and is currently still on this therapy regime. Although having not been studied systematically, the case presented here demonstrates that TTFields therapy may be considered for newly diagnosed and recurrent glioblastoma patients with previously diagnosed multiple sclerosis.